2014
DOI: 10.3109/19401736.2014.958674
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome of the pink bollworm Pectinophora gossypiella (Lepidoptera: Gelechiidae)

Abstract: Pectinophora gossypiella (Lepidoptera: Gelechiidae) is a key pest in many cotton-growing countries of the world. In this study, the complete mitochondrial (mt) genome of the pink bollworm P. gossypiella was determined, which is 15,202 bp in length (GenBank accession number: KM225795) containing 37 typical animal mitochondrial gene and an A + T-rich region. The gene order of P. gossypiella mtDNA was different from the insect ancestral gene order in the translocation of trnM, as shared by previously sequenced le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…The gene arrangement of H. kurokoi is identical to that of other ditrysian Lepidoptera, including gelechioids, that have the order trnM-trnI-trnQ (where the underline indicates a gene inversion) between the A þ T-rich region and ND2 (Kim et al 2011;Park et al 2016;Timmermans et al 2014;Zhao et al 2016), instead of the ancestral trnI-trnQ-trnM order found in the majority of insects (Boore 1999).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…The gene arrangement of H. kurokoi is identical to that of other ditrysian Lepidoptera, including gelechioids, that have the order trnM-trnI-trnQ (where the underline indicates a gene inversion) between the A þ T-rich region and ND2 (Kim et al 2011;Park et al 2016;Timmermans et al 2014;Zhao et al 2016), instead of the ancestral trnI-trnQ-trnM order found in the majority of insects (Boore 1999).…”
mentioning
confidence: 77%
“…and Nepticuloidea (Stigmella roborella) were included as outgroups. GenBank accession numbers are as follows: Urodus decens, KJ508062 (Timmermans et al 2014); Adoxophyes honmai, DQ073916 (Lee et al 2006); Ethmia eupostica, KJ508047 (Timmermans et al 2014); Perimede sp., KJ508041 (Timmermans et al 2014); Endrosis sarcitrella, KJ508037 (Timmermans et al 2014); Promalactis suzukiella, KM875542 (Park et al 2014); Oegoconia novimundi, KJ508036 (Timmermans et al 2014); Atrijuglans hetaohei, KT581634 (Unpublished); Pectinophora gossypiella, KM225795 (Zhao et al 2016); Tineola bisselliella, KJ508045 (Timmermans et al 2014); Phyllonorycter froelichiella, KJ508048 (Timmermans et al 2014); Astrotischeria sp., KJ508056 (Timmermans et al 2014); and Stigmella roborella, KJ508054 (Timmermans et al 2014). …”
Section: Disclosure Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…to 15,408 bp (Oegoconia novimundi) (Timmermans et al 2014;Park et al 2016a, b;Zhao et al 2016). The gene arrangement of S. auriferella was identical to that of other ditrysian Lepidoptera, including gelechioids.…”
Section: Article Historymentioning
confidence: 99%
“…It is the second most species-rich group of Lepidoptera (van Nieukerken et al 2011) that is important to attaining a better understanding of higher-level phylogeny van Nieukerken et al 2011). Nevertheless, prior to this study, only eight mitochondrial genomes (mitogenomes) have been sequenced (Timmermans et al 2014;Park et al 2016a, b;Zhao et al 2016). Greater focus on additional species from a diverse taxonomic group is essential to conduct comprehensive mitogenome-based phylogenetic studies on Lepidoptera (including Gelechioidea).…”
mentioning
confidence: 99%